The Influence of Self-Efficacy on Employee Performance Mediated by Employee Loyalty (Courtiers) in the Yogyakarta Palace - Diah Retno Wulandaru; Sri Rahayu Ningtiyas; Rifqi Syarif Nasrulloh (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: The purpose of this study is to examine and prove the effect of self-efficacy on employee performance, with job loyalty as a mediating variable, on employees (courtiers) at the Yogyakarta Palace. Methodology: This study uses a quantitative approach through the type of primary data with a population consisting of 416 employees from four divisions in the Yogyakarta Palace. The research sample of 100 employees (courtiers) was selected using random sampling technique. Data analysis was carried out using the Structural Equation Modeling (SEM) Partial Least Square (PLS) method using Smart PLS 4 software. Results: The results showed that self-efficacy has a significant effect on employee performance, job loyalty also has a significant effect on employee performance, and self-efficacy has a significant effect on job loyalty. However, the effect of self-efficacy on employee performance through work loyalty as a mediating variable is not significant. Conclusions: Employees (courtiers) with stronger beliefs in self-efficacy tend to have better performance and also higher loyalty to the organization. This research shows that the loyal attitude of courtiers based on a sense of love and belonging to the culture and traditions of the Yogyakarta Palace is an attitude of self-devotion, not a factor of work loyalty in general. Building self-efficacy in courtiers is very important to increase their loyalty and performance at work. Limitations: First, because this study only looks at the relationship between variables that are still limited. Second, the sample used may be limited to a particular sector, so the results cannot be generalized to various organizational contexts. Contribution: It is important to maintain the existing vocational training and mentoring. Strengthen the existing job training and mentoring system in the Palace as an effort to align with cultural challenges in this era of modernization..